O papel do PROCON na defesa qualificada dos interesses dos consumidores: o acesso à justiça e os métodos alternativos de resolução de conflitos de consumo - Britto, Igor Rodrigues (2009)
It shows that the consumer society has witnessed the emergence of new configurations of legal relations, a fact that makes it imperative to rethink the traditional models, now obsolete, of protecting consumer rights. It denounces the deficient positive performance of the State in protecting and enforcing consumer rights, which raises one of the main obstacles to the realization of the fundamental right of access to justice at the end of the 20th century: the “organizational obstacle”. Makes notes on the most outstanding policy of access to justice developed to date: the universal access to justice movement, tested by Mauro Cappelletti. After emphasizing the commitment of the so-called “Florentino Project” with the identification of the causes and effects produced by the economic, organizational and procedural obstacles to the exercise of the fundamental right of access to justice, it seeks, in the context of the second wave of the movement (dedicated to order obstacles) organizational), justifications for the importance: of the advent of the Consumer Protection Code; the constitutional postulate of consumer protection (Article 5, XXXII); and, finally, the role of PROCONS. He points out that, in the midst of the “crisis in the administration of justice”, these organs of direct administration of the State and Municipal Executive Powers are instituted in Brazil with the mission of mitigating the effects produced by the ineffectiveness of the State in protecting consumer rights. It highlights the fact that the popularization of PROCONS as an instance of resolving individual conflicts, is largely due to the expressive results (at least quantitatively) achieved through the so-called “conciliation hearings”. Subsequently, while emphasizing the celebrated indexes of agreements signed by the agents of these bodies, it points out technical and functional irregularities in the exercise of a function that is not their responsibility: that of conciliators. Thus, while investigating the convenience and adequacy of the use of reconciliation techniques by these agents, it faces the central problem of this essay, committed to the search for answers to the following questions: a) it can be said that the use of conciliation in the pacification of consumer conflicts ?; and b) is it correct to talk about the training of PROCONS agents for the use of conciliation techniques, or would there be other techniques more indicated in the exercise of their task? After exploring theoretical and practical precepts regarding alternative methods of conflict resolution in Brazil, based on the assumption that it is the duty of PROCONS and their agents, to promote the protection and defense of consumer rights (with absolute partiality and priority, under the terms of Constitution), defends the thesis that its agents, who act as conciliators by virtue of infra-constitutional laws, should play a more active role in negotiating the interests of those they effectively represent, that is: the negotiating office. Finally, he argues that, once encouraged and prepared to endure the assisted negotiation of the interests of the category they represent, PROCONS 'employees would better (qualitatively) perform their functions as agents that facilitate access to justice, without prejudice to the practice of administrative actions by prevention of other extended or diffuse consumer conflicts.